NAVIGATING ECO-GRIEF: READING THE INTERSECTION OF WOMEN AND THE ROLE OF MEDIA IN PROVIDING MENTAL SOLACE - Das, Rupam Kr.; Priyanka Kalita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Global environmental degradation and its implications on mental health off late has been receiving scholarly attention. The lived experience of environmental pain and its associated notion, Eco-Grief, is used to describe the long-term emotional impact of environmental and climate change-related disasters. Eco-Grief refers to a deep sense of sorrow brewing from environmental degradation and concerns about potential future ecological damage. These intense emotions, also known as "eco-mourning," can drastically affect the mental well-being, especially during times of alarming global events like pandemic and several other climate crises. Historically, women have been acknowledged for their crucial roles in environmental preservation. As women are closely connected to nature, they often suffer the most during climate crisis. Women’s strong bond with the environment makes them more vulnerable to the impacts of environmental degradation and natural disasters. The effects of the climate crisis on them are not only physical but it also triggers a deep sense of emotional responses like sadness, helplessness, guilt, anxiety, numbness etc. In society, though the media primarily provides information, education and entertainment, it also serves as a tool for recreation and fulfilling cognitive and emotional needs. In this context, the paper aims to explore how the media can console women experiencing eco-grief and examine the potential of media assistance in navigating these arduous emotional encounters. Furthermore, it shall examine how the coverage of the media on environmental issues can lessen the intensity of eco-grief. In the process, the role of social media campaigns, awareness programmes and documentaries in raising awareness and providing coping mechanisms shall be extensively investigated through the lens of eco-grief.